Discontinuous dynamic recrystallization behavior and texture evolution of large-size pure titanium flat ingot via electron beam cold hearth melting during short process direct hot rolling - Xiaolin Liu; Peizhen Wang; Yaming Shi; Junsheng Wang; Yuqin Zhang; Yehua Jiang (Journal of Materials Research and Technology, 2024)
Large-size pure titanium ingots melted by single electron beam cold hearth melting (EBCHM)) could be rolled into large-width and heavy-weight titanium strip coils using short process without forging. It is crucial to study the large-span refinement mechanism from highly coarse grains, whose sizes are in the order of ∼cm, to micronmeter. In this study, the recrystallization mechanism and texture evolution of pure titanium with a size of 1570 × 200 × > 8000 mm was investigated by multi-pass simulated rolling and experimental rolling. The results indicated the hot deformation can result in marked reduction in grain size of the as-cast grain, from 3 to 5 cm to 17–23 μm. The discontinuous dynamic recrystallization (DDRX) mechanism of a pure titanium ingot during direct multi-pass hot deformation causes the reconstruction of as-cast microstructure and refinement of hot rolling microstructure. Furthermore, DDRX occurred, during hot deformation, and was accompanied with weakening of deformation texture. Raising the initial hot deformation temperature results in a modification of the texture type of the {0001} crystal plane. The strength of the texture experiences a decrease initially and then eventually an increase. This alteration in strength is inversely related to the degree of dynamic recrystallization. Based on the simulated rolling experiment, the results of experimental rolling also found the coarse as-cast grains was broken and reconstructed. It has strength (average yield strength: 334 MPa, ultimate tensile strength: 371 MPa), ductility (total elongation: 30 %). Such a combination of mechanical properties makes the hot rolling plate a potential choice for sheet practical application.